Design and Performance Evaluation of a 200 Wp Off-Grid Solar Photovoltaic Module for Renewable Energy in Indonesia - Sitorus, Nobert; Ginting, Berta Br.; Panjaitan, Berman P.; Simanjuntak, Benrad E.; Naibaho, Penteris R. P.; Matondang, Aprima A.; Simanjuntak, Andrean V. H. (UIR PRESS, 2025)
The rapid growth of global energy demand and the urgent need to reduce greenhouse gas emissions have accelerated the transition toward renewable energy technologies, with solar photovoltaic (PV) systems playing a central role. In Indonesia, high solar irradiation provides significant potential for PV adoption, yet challenges remain in human resource capacity and technical readiness, particularly in rural areas where off-grid systems are critical. This study presents the design, development, and testing of a 200 Wp off-grid PV training module aimed at bridging the gap between theoretical knowledge and practical skills in renewable energy education. The module integrates two 100 Wp PV panels, a 100 Ah lithium-ion battery, an MPPT charge controller, and a 500 W pure sine wave inverter, all mounted on a modular acrylic platform to enable repeated assembly and disassembly for training purposes. Experimental testing under tropical conditions demonstrated stable PV output (Voc 19.8–21.5 V, Isc 4.8–5.4 A), efficient battery charging within 8 hours to full capacity, and reliable discharging performance sustaining DC loads for 18 hours and AC loads for 12–14 hours. Inverter efficiency averaged 92%, with minimal waveform distortion under typical loads. These results confirm the module’s reliability and educational value, offering a robust platform for vocational training and community-based capacity building. The study contributes to Indonesia’s renewable energy transition and supports Sustainable Development Goal 7 by enhancing technical education and workforce readiness for solar PV deployment.